Numerical simulation of non-reacting fuel-air coaxial jets by means of a novel high-order method. (15th February 2021) - Franchina, N.; Savini, M.; Bassi, F.
Highlights: High-order accurate computations of mixing characteristic of coaxial, non reactive, jets. Stoichiometric mixing length computed by means of DG computations. CFD study of round jets, annular and round wakes compared to experiments. Abstract: The present work deals with the development of an original Discontinuous Galerkin (DG) finite element code and its application to compute the non-reactive aerodynamics of multicomponent gaseous mixtures in turbulent regime. Recent developments of the DG approach show great potential in computing high-order accurate solutions on arbitrarily complex grids even in the presence of strong discontinuities and thus the method is well suited for modeling combustion aerodynamics. The study of coaxial jets, with and without swirl, is indeed of paramount importance in assessing burner and combustor performance and the accurate understanding of their fluid dynamic behaviour is an essential prerequisite to subsequently investigate their reactive counterpart. The predictive capabilities of the novel method proposed are verified against several experimental tests taken from three different databases, selected to cover the widest range of coaxial jets operating conditions, and compared with simulations carried out using a commercial code, at most second-order accurate. Notwithstanding the numerical prediction of turbulent gaseous mixture is indeed challenging, it is shown that the DG method exhibits a good accuracy level even on coarse grids and allows to properly resolve the relevant jet structures and characteristic features.